1987
DOI: 10.1079/bjn19870092
|View full text |Cite
|
Sign up to set email alerts
|

Effects of early-life undernutrition in artificially reared rats: subsequent body and organ growth

Abstract: I. Four groups of rat pups were reared: mother-reared (MR) control (well-fed) and undernourished (MRC and MRU respectively) and artificially reared (AR) control and undernourished (ARC and ARU respectively). Pups for artificial rearing were fitted with a gastric cannula on postnatal day 5 and were fed, by intermittent gastric infusion, expressed rats' milk (days 5-7), mixtures of rats' milk and milk-substitute (days 8-16), and milksubstitute only (days 17-20). Solid food was available to MR pups throughout and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…In humans, the metabolic demands of breastfeeding require an increase in maternal metabolism of approximately 20% or less (Frigerio et al , 1991; Prentice and Whitehead, 1987). This contrasts markedly with laboratory rodents, where nutrient intake is critical for lactation success because a large portion of the metabolic output is directed to milk synthesis (Grigor et al , 1987; Smart et al , 1987). …”
Section: Resultsmentioning
confidence: 97%
“…In humans, the metabolic demands of breastfeeding require an increase in maternal metabolism of approximately 20% or less (Frigerio et al , 1991; Prentice and Whitehead, 1987). This contrasts markedly with laboratory rodents, where nutrient intake is critical for lactation success because a large portion of the metabolic output is directed to milk synthesis (Grigor et al , 1987; Smart et al , 1987). …”
Section: Resultsmentioning
confidence: 97%
“…1A) through which the milk substitute is pulse‐fed from an infusion syringe for up to 30 min in each hour over the 24‐hr day before the milk is replenished and the system maintained. AR rats can be weaned from the milk substitute at 19–20 days of age to develop to adulthood (Smart et al, 1987, 1989). This model eliminates variables introduced from maternal influences because the mother rat is not a component of the test or control groups (O'Connor et al, 1988).…”
Section: Methodsmentioning
confidence: 99%
“…It is becoming clear that early nutrition in the critical period plays an important role in the long-term health and neuro-development. Experimental studies in animals have shown that nutrition in the critical period of life can affect brain structure and function irreversibly [11,12]. Postnatal nutrition in rat male pups was shown to affect dendritic branching in certain locations of rat brain, important in regulating attention status and the integration of motor and sensory activity, and this effect persisted in spite of later correction of nutritional deficits [13].…”
Section: Pn In Premature Neonatesmentioning
confidence: 99%